2022
DOI: 10.1039/d2ta01045c
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the shell thickness and shell components in PtCu/PdCu core–shell tripods for ethylene glycol and glycerol oxidation reactions

Abstract: Bi−component core−shell catalysts constructed from both noble and transition metals have been widely used in alcohol oxidation reactions, especially the introduction of transition metal components that can improve the anti−poisoning...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…It was previously suggested that Ir was easy to transform into IrO 2 under electro-oxidation, which was a more active and stable species for electro-catalysis. 50 However, the oxidation of Ru was accompanied by over-oxidation to form hypervalent RuO 4 with feeble activity and strong dissolvability. 51 This could explain why the Ir x Ru 1− x nanocages with x ≥ 0.5 exhibited much better stability: more than half of Ir content in Ir x Ru 1− x nanocages produced a large proportion of Ir 4+ , thus reducing the percentage of as-formed RuO 4 and guaranteed the stability for both the HER and the OER.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously suggested that Ir was easy to transform into IrO 2 under electro-oxidation, which was a more active and stable species for electro-catalysis. 50 However, the oxidation of Ru was accompanied by over-oxidation to form hypervalent RuO 4 with feeble activity and strong dissolvability. 51 This could explain why the Ir x Ru 1− x nanocages with x ≥ 0.5 exhibited much better stability: more than half of Ir content in Ir x Ru 1− x nanocages produced a large proportion of Ir 4+ , thus reducing the percentage of as-formed RuO 4 and guaranteed the stability for both the HER and the OER.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this strategy can potentially be used to synthesize multi-component core-shell structures like PtCu/ MCu (M: Rh, Ru, Au, Ir). 105 Non-noble transition metal based electrocatalysts. Transition metal-based compounds have been used in various processes ranging from N 2 reduction, CO 2 reduction, and H 2 production through photo-/electrocatalytic, thermocatalysis, and other industrial processes.…”
Section: Pd Based Electrocatalystsmentioning
confidence: 99%
“…Interestingly, this strategy can potentially be used to synthesize multi-component core–shell structures like PtCu/MCu (M: Rh, Ru, Au, Ir). 105…”
Section: Electrocatalytic Valorization Of Glycerolmentioning
confidence: 99%
“…S4f, ESI †). 19 Interestingly, compared to the XPS spectra of DP-HEA/CNFs (Figs. S4b-f, ESI †), the 2p 3/2 peaks from Fe, Co, Ni, Cu and the 3d 5/2 peak from Pd s in DP-B-HEA/CNFs shifted to the higher BEs (0.3 eV).…”
mentioning
confidence: 99%